2014
DOI: 10.1177/0890334414558847
|View full text |Cite
|
Sign up to set email alerts
|

Working Mothers of the World Health Organization Western Pacific Offices

Abstract: Optimal breastfeeding saves lives. However, suboptimal breastfeeding is prevalent, primarily resulting from inappropriate promotion of infant formula and challenges of working mothers to continue breastfeeding. The article aims to determine the extent to which World Health Organization (WHO) policies protect, promote, and support breastfeeding women working at the WHO, Western Pacific Region. An online survey targeted all female WHO and contractual staff in all country and regional offices, who delivered a bab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The importance of early initiation of breastfeedingis well recognised [2, 30, 33]. In the current study, nearly all working mothers (91 %) initiated breastfeeding within the first one hour of delivery.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The importance of early initiation of breastfeedingis well recognised [2, 30, 33]. In the current study, nearly all working mothers (91 %) initiated breastfeeding within the first one hour of delivery.…”
Section: Discussionmentioning
confidence: 56%
“…It is worthy of note that, in Ghana, this period is limited to only three months by law, which is far too short for a working mother to practice exclusive breastfeeding to six months, making the practice a challenge. In Western Pacific settings, maternity leave extends to sixteen weeks [2] but other studies in Taiwan cited that most companies provide only eight weeks of maternity leave [40]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the effectiveness of workplace policies that support breastfeeding, the WHO surveyed their staff in their Western Pacific offices on how employers could better support breastfeeding practices (Iellamo, Sobel, & Engelhardt, 2015). They found that WHO employees faced obstacles similar to those of other employed mothers.…”
Section: Workplace Policiesmentioning
confidence: 99%
“…3 Of the approximately 135 million babies born every year world-wide, only 39% are exclusively breastfeeding during the first 6 months; and more than 800,000 deaths in children under age 5 years are also attributed to suboptimal breastfeeding. 5 In the United States, the rate of exclusive breastfeeding for the first six months is at 16.4% and is slowly rising, but the rate remains well below the Healthy People 2020 target goal of 25.5%. 1 According to the National Immunization Survey, 80% of infants in the United States are breastfed with only 21.9% exclusively breastfeeding at 6 months.…”
Section: Introductionmentioning
confidence: 99%